2023
DOI: 10.3390/microorganisms11082035
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbial Network Analysis Reveals Novel Taxa Relationships among Adolescent and Young Women with Incident Sexually Transmitted Infection Compared with Those Remaining Persistently Negative over a 30-Month Period

Abstract: A non-optimal vaginal microbiome (VMB) is typically diverse with a paucity of Lactobacillus crispatus and is often associated with bacterial vaginosis (BV) and sexually transmitted infections (STIs). Although compositional characterization of the VMB is well-characterized, especially for BV, knowledge remains limited on how different groups of bacteria relate to incident STIs, especially among adolescents. In this study, we compared the VMB (measured via 16S ribosomal RNA gene amplicon sequencing) of Kenyan se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The possible mechanism of the association between UU infection and abnormal cervical cytopathology might be related to the combination of several complex infection-associated inflammatory responses, involving production of reactive oxidative metabolites, increased expression of cytokines, chemokines and growth and angiogenic factors, decreased cell-mediated immunity, and the generation of free radicals [40,46]. The large meta-analysis of Liang et al concluded that, together with bacterial vaginosis (BV), CT, and reduction in Lactobacilli, UU are also associated with increased risk of HPV infection and CIN development [40,47,48].…”
Section: Bacterial Stis and Ureaplasma Spp In Particular As A Potenti...mentioning
confidence: 99%
“…The possible mechanism of the association between UU infection and abnormal cervical cytopathology might be related to the combination of several complex infection-associated inflammatory responses, involving production of reactive oxidative metabolites, increased expression of cytokines, chemokines and growth and angiogenic factors, decreased cell-mediated immunity, and the generation of free radicals [40,46]. The large meta-analysis of Liang et al concluded that, together with bacterial vaginosis (BV), CT, and reduction in Lactobacilli, UU are also associated with increased risk of HPV infection and CIN development [40,47,48].…”
Section: Bacterial Stis and Ureaplasma Spp In Particular As A Potenti...mentioning
confidence: 99%